Public service delivery and free riding: Experimental evidence from India - Alex Armand; Britta Augsburg; Antonella Bancalari (Institute for Fiscal Studies (IFS), 2022)
This paper provides novel evidence on the trade-off between public service delivery and free riding in low- and middle-income countries. We implement a field experiment in the slums of two major Indian cities, where inadequate access to sanitation restricts residents to either free ride, by disposing human waste in common-property areas, or use a fee-funded public service provided by community toilets. Using original survey, behavioral and objective measurements, we show that top-down incentives for the quality of service provision improves delivery and reduces non-payment of fees, but excludes a share of residents from using the service, forcing them into free riding. Willingness to pay for the service is unaffected, but demand for public intervention in the quality of delivery increases, replacing the demand to address free riding. Adding a campaign sensitizing the consequences of free riding among residents raises awareness, but does not induce any behavioral change. Supplementing reduced form estimates with structural estimates, we show that eliminating free riding requires subsidizing use beyond free basic services.
Keywords: C93; H40; I15; Q53; 330; ublic service; basic services; infrastructure; maintenance; free riding; willingness to pay; water and sanitation; information; health